Seeking forgiveness in an intergroup context: angolan, guinean, mozambican, and east timorense perspectives - Félix Neto (2007)
Forgiveness is a key concept in many governance and responsive regulation issues. The notion of intergroup forgiveness was examined among people from four countries: Angola, Guinea-Bissau, Mozambique, and East Timor. Nine hundred and eighty-five adults who had suffered from the many conflicts in their areas, either personally or through injuries inflicted on members of their family, agreed to participate in a study that was specifically about seeking intergroup forgiveness. In all four countries, most participants of the study agreed with the ideas that (i) seeking intergroup forgiveness makes sense; (ii) the seeking process must be a popular, democratic, and public process, not a secret elite negotiation; (iii) the process must be initiated and conducted by people in charge politically, not by dissident factions; and (iv) the process is aimed at reconciliation, not at humiliating the group requesting forgiveness. Differences between the four countries were found regarding the extent to which (i) international organizations may be involved in the process; (ii) the demand must include the former perpetrators; and (iii) emotions and material compensation are ingredients in the process.